Elements of Iranian Cultural Identity; Sample Analysis in Document of "Components of Iranian National Identity" - Ali Karimi Maleh; Meisam Belbasi; Seyyed Mohammad Javad Ghorbi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2018)
This article seeks to answer the question of which layers and elements are the cultural identity of the Islamic Republic of Iran in the document "Elements of Iranian National Identity"? The achievements of this research show that cultural identity in the document of the elements of Iranian national identity consists of two layers of Islamic cultural identity including elements such as spirituality and monotheism, Islam and the religion of Shiism and Quranic education, cultural convergence, the elimination of oppression and oppression, Ordinary, ethics, customs, and traditions, the practice of the Prophet's sake, is the never-ending justice, expectation and historical mission of the Iranian people, and the cultural identity of Iranians including elements such as cultural heritage and ritual, Iranian architecture, Scholars and science-friendship, Iranian history, defense of the land, memory and collective memories, Iranian civilization, Persian language and Persian font, Iranian ethnos and groups with beautiful subcultures that can lead to the cultural, spiritual and national identity and solidarity among the Iranian people. It should also be noted that the document does not mention any modern Iranian identity. To answer the question, a qualitative and quantitative content analysis method is used.